The Residence of Catholic Missionaries in Georgia according to Textual and Visual Narratives by Christoforo De Castelli - Chikhladze, Marietta (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2017)
This article aims to analyze and compare the narrative forms of textual and visual works by Cristoforo De Castelli (1600-1659), the Sicilian missionary in Georgia, who left behind rich materials on the 17th century period of that country. The works of Castelli include letters, reports and drawings, created throughout his twenty-five-year stay in Georgia. Sent to Rome as independent compositions the works were collected and organized into seven thematically and chronologically ordered albums by Castelli upon his return to his hometown of Palermo (1656-1658), where the manuscripts are kept today. Other works (letters and reports) are scattered in different archives and libraries in Italy (Rome, Florence and Naples). Yet, as a single narrative it combines Castelli’s life throughout his mission in Georgia with his reflections on the realities of the country.